2017
DOI: 10.20517/2394-4722.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

A new twist to neurotransmitter receptors and cancer

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 3.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Nicotine’s effect likely involves the epidermal growth factor receptors (EGFRs), since it has been previously reported that nicotine induces secretion of growth factors leading to tumor progression and metastasis [ 7 ]. Binding of nicotine to α7nAChRs can induce the secretion of growth factors, such as EGF, IGF, along with neurotransmitters, such as adrenaline and noradrenaline [ 7 , 48 ]. This nicotine-mediated increased secretion of EGF and IGF leads to the transactivation of EGFR and IGF-1R, resulting in the activation of mitogenic and antiapoptotic pathways [ 7 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine’s effect likely involves the epidermal growth factor receptors (EGFRs), since it has been previously reported that nicotine induces secretion of growth factors leading to tumor progression and metastasis [ 7 ]. Binding of nicotine to α7nAChRs can induce the secretion of growth factors, such as EGF, IGF, along with neurotransmitters, such as adrenaline and noradrenaline [ 7 , 48 ]. This nicotine-mediated increased secretion of EGF and IGF leads to the transactivation of EGFR and IGF-1R, resulting in the activation of mitogenic and antiapoptotic pathways [ 7 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Binding of nicotine to α7nAChRs can induce the secretion of growth factors, such as EGF, IGF, along with neurotransmitters, such as adrenaline and noradrenaline [ 7 , 48 ]. This nicotine-mediated increased secretion of EGF and IGF leads to the transactivation of EGFR and IGF-1R, resulting in the activation of mitogenic and antiapoptotic pathways [ 7 , 48 ]. Moreover, release of adrenaline and noradrenaline, the physiological ligands for β-AR, upon binding of nicotine to α7nAChRs, activates the β-AR which, in turn, stimulates release of EGF and IGF, thereby promoting growth and proliferation contributing to lung cancer progression [ 7 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary neuroepithelial bodies (NEB) are innervated serotonin (5-HT)-producing cells distributed throughout the airway epithelium. Studies have reported that 5-HT secretion can stimulate cancer progression, including cancer proliferation, migration, and invasion [ 20 , 21 ]. The data in Figure 1 provide evidence that AZ, SFN, and their combination show dose-dependent reduction in scratch wound closure by the bronchial carcinoid H727 (typical carcinoid) cells.…”
Section: Resultsmentioning
confidence: 99%
“…Neurotransmitter signaling can modulate different aspects of cancer development, such as proliferation, invasion, metastasis [221,222,223,224]. (See BOX 2 for autonomic pancreatic innervation [225,226]).…”
Section: Molecules and Pathways Involved In Pnimentioning
confidence: 99%